Determination of Thorium in Geochemical Samples by Inductively Coupled Plasma-Atomic Emission Spectrometry - WANG Jun; WANG Di; DENG Chang-sheng; ZHANG Jian-mei; YANG Dong; WANG Bin-tang; ZHU Su-xia (Yankuang ceshi, 2014)
Thorium in geological samples, digested by mixed acid system of HNO3-HCl-HClO4-HF, is measured by using Inductively Coupled Plasma-Atomic Emission Spectrometry (ICP-AES). In the practical analysis, the stability of the results is poor when the content of thorium, moreover, the content of thorium cannot be detected with high matrix effect. In this work, a new method is described for the determination of thorium using ICP-AES. The pretreatment process is optimized by digestion with Na2O2, filtration separated with 10 g/L NaOH and resolved with 40% hot HCl acid. The best analytical line of thorium is 401.913 nm by studying the working conditions of ICP-AES. The method detection limit is 0.21 μg/g, the relative standard deviation (n=7) are from 7.7% to 15.9%, the relative error (n=6) are from 7.0% to 10.0%, and the standard addition recovery are from 92.0% to 104.0%. Furthermore, this method can be used to determine accurately the content of thorium, which is higher than 0.21 μg/g based on verification of certified reference materials. Compared with conventional methods, this method is simple, fast, and highly accurate and has a lower detection limit. It is suitable for practical determination of a large amount of samples.